Defining crime: a critique of the concept and its implication - Lynch, Michael J. (Palgrave Macmillan, 2015)
"Defining Crime explores the limitations of the legal definition of crime, how that politically based definition has shaped criminological research, and why criminologists must redefine crime to include scientific objectivity. Lynch, Stretesky, and Long argue that a scientific definition of crime must be detached from criminal law and the variation the political construction imposes. The authors propose an alternative definition of crime, explore its limitations, and how it can reshape criminological research"--